Research and Analysis of Factors Influencing the Passing Rate of CET-4 in Local Universities - Sana; Chang Lin; Chen Shaozu; Gao Hui (Lavai)
With the rapid development of social information and economic globalization, English has become widely prevalent worldwide. As a "global language," English significantly influences language teaching policies and practices globally, particularly in China, where a national College English Test Band-4 has been established. Since its inception, the College English Test Band-4 has evolved into one of the most crucial assessments for evaluating college students’ foreign language proficiency. Recently, a growing number of local university students in China are grappling with the challenge of failing to pass this exam. Therefore, this study examines the influencing factors on the passing rate of the College English Test Band-4, based on surveys conducted among undergraduate students in 2020 and 2021 at Hulunbuir College. The paper employs cross-analysis and regression tests to analyze the factors affecting the passing rate of CET-4 among local undergraduate college students, drawing relevant conclusions. Additionally, the study proposes suggestions for English learning strategies tailored to the needs of local undergraduate college students. Factors such as gender, English scores in the college entrance examination, and daily English learning methods are identified as having a significant impact on the passing rate of CET-4.